Correlations of handgrip strength with selected hand-arm-anthropometric variables in Indian inter-university female volleyball players - Koley, S.; Kaur, S. P. (Asian Journal of Sports Medicine, 2011)
Purpose: The purpose of this study was to estimate the dominant handgrip strength and its correlations with some hand and arm anthropometric variables in 101 randomly selected Indian inter-university female volleyball players aged 18-25 years (mean age 20.52 ± 1.40) from six Indian universities.